Pharmacogenomics of TNF inhibitors - Jan, Zainab; El Assadi, Farah; Velayutham, Dinesh; Mifsud, Borbala; Jithesh, Puthen Veettil (Frontiers in Immunology, 2025)
Tumor necrosis factor alpha inhibitors (TNFi) are biologic drugs that target TNFα, a key pro-inflammatory cytokine, to suppress disease activity and alleviate symptoms of various autoimmune diseases, including inflammatory bowel disease. This review focuses on the five US FDA-approved TNFi including the monoclonal antibodies Infliximab, Adalimumab, Golimumab, Certolizumab pegol and the soluble TNFα receptor fusion protein Etanercept, with a brief mention of other available biosimilars to TNFi. The review aims to summarize the recent evidence on the pharmacokinetics, pharmacodynamics, and pharmacogenomics of TNFi with a particular focus on Human Leukocyte Antigen (HLA) variants in terms of their genetic contribution to the response to TNFi. HLA variants have been linked to heterogeneity in the efficacy and safety of TNFi among patients. Building on the summarized evidence, the last part of the review discusses the potential clinical utility of testing for pharmacogenetic variants that are linked to the response to TNFi prior to the drug prescription, and it also addresses the future directions to achieve personalized treatment for TNFi users.